IMPROVING THE ABILITY OF READING DESCRIPTIVE TEXT THROUGH STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TECHNIQUE - ., Kurniawati; Susilawati, Endang; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: MeningkatkanKemampuanMembacaTeksDeskriptifmelaluiTeknikStudent Team Achievement Divisions (STAD).Tujuandaripenelitianiniadalahuntukmemecahkanmasalahprestasisiswadan proses belajarmengajarmembacateksdeskriptifmelaluiStudent Team Achievement Divisions (STAD) teknik. Penelitianinidilakukandenganmenggunakanpenelitiantindakankelas.Berdasarkanhasilpengamatansiklus 1 sampai 3, penulismenyimpulkanbahwasikapdansiswasiswakemampuanmembacateksdeskriptif yang berlangsungbaiksetelahdiajarkanmelaluiteknik STAD.Tingkat minimum melewatiskorpadaketerampilanmembacateksdeskriptifdidasarkanpada KKM (KriteriaKetuntasan Minimal) di kelas XI MAS Al-Ishlah Pontianak itu 60.Memperhatikanpeningkatannilaidansikapsiswa, penulismenyimpulkanbahwakemampuanmembacateksdeskriptifsetelahdiajarkanmelaluiteknikStudent Team Achievement Divisions (STAD) dapatmeningkatkansukses. Kata kunci: membaca teks deskriptif, teknik STAD Abstract:Improving the Ability of Reading Descriptive Text through Student Team Achievement Divisions (STAD) Technique.The purpose of this research was to solve the problem of students achievement and teaching learning process of reading descriptive text through Student Team Achievement Divisions (STAD) technique.This research was conducted using a classroom action research. Based on the result of the observation of cycle 1 to 3, the writer concluded that the students attitude and the students ability of reading descriptive text were in good progress after being taught through STAD technique. The minimum level of passing score on reading skill of descriptive text was based on KKM (KriteriaKetuntasan Minimal) at the eleventh grade of MAS Al-Ishlah Pontianak that was 60. Noticing the increasing of students score and attitude, the writer concluded thatthe ability of reading descriptive text after being taught through the technique of Student Team Achievement Divisions (STAD) can improve successfully. Key words: reading descriptive text, STAD technique